Peran PKBM Ulil Absor Dalam Meningkatkan Life Skill Masyarakat di Desa Jago Kecamatan Praya Kabupaten Lombok Tengah - Hasrin, Dedy; Fakhri, Moh; Hidayati, Dahlia (TAMADDUN: Jurnal Ilmu Sosial, Seni, dan Humaniora, 2025)
PKBM Ulil Absor in Jago Village, Praya District, Central Lombok Regency, plays a crucial role in improving the quality of life for the community through non-formal education programs, particularly in developing life skills. Programs such as sewing and welding courses provide practical skills that can be directly applied in daily life, helping to reduce unemployment and boost the local economy. Despite its progress, PKBM faces several challenges, including board members holding multiple positions and limited support from the community and government. To ensure the sustainability of the programs, improvements in board professionalism, better community outreach, and increased government support are necessary. This article discusses the role of PKBM Ulil Absor in community empowerment, the challenges it faces in implementation, and offers recommendations for further development to enhance the effectiveness and impact of the programs.